2021
DOI: 10.1016/j.anaerobe.2021.102379
|View full text |Cite
|
Sign up to set email alerts
|

A cortex-specific penicillin-binding protein contributes to heat resistance in Clostridioides difficile spores

Abstract: Background Sporulation is a complex cell differentiation programme shared by many members of the Firmicutes, the end result of which is a highly resistant, metabolically inert spore that can survive harsh environmental insults. Clostridioides difficile spores are essential for transmission of disease and are also required for recurrent infection. However, the molecular basis of sporulation is poorly understood, despite parallels with the well-studied Bacill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…2g ). Moreover, in agreement with a previous study 33 , C. difficile SpoVD localizes to polar septa during asymmetric division (Supplementary Fig. 9 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…2g ). Moreover, in agreement with a previous study 33 , C. difficile SpoVD localizes to polar septa during asymmetric division (Supplementary Fig. 9 ).…”
Section: Resultssupporting
confidence: 93%
“…2a, b ), indicating that C. difficile SpoVD and SpoVE are not involved in vegetative cell division. Consistent with prior work 32 , 33 , the C. difficile ∆ spoVD strain failed to make heat-resistant spores (Supplementary Fig. 3 ) or synthesize a cortex layer based on transmission electron microscopy (TEM) analyses (Supplementary Fig.…”
Section: Resultssupporting
confidence: 85%
“…Raman spectroscopy can determine the content of different chemical groups in biological tissues using the peak positions and peak intensity values, which meet the above requirements. 31–33…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy can determine the content of different chemical groups in biological tissues using the peak positions and peak intensity values, which meet the above requirements. [31][32][33] In this study, the objective was to provide a new method for spore purication during the coexistence of the spores and vegetative cells, which is based on a "stepped" magnetic ow device combined with an antibiotic affinity strategy for directly purifying spores. The "stepped" internal structure increased the contact area and collision probability between the sample and the magnetic site, which could be used for spore purication in complex microbiological samples without blockage.…”
Section: Introductionmentioning
confidence: 99%
“…Cd SpoVD is essential for spore production, as interruption of the CdspoVD gene results in no spores being formed . Furthermore, Cd SpoVD activity is necessary for the production of the spore cortex, where PBPs, like Cd SpoVD, cross-link glycan chains of peptidoglycan . Further research showed that cephamycins (cefotetan, cefoxitin, and cefmetazole) can induce an antispore effect in vitro as well as prevent CDI relapse in in vivo models of disease.…”
Section: Introductionmentioning
confidence: 99%